Cardiac echinococcosis with intra-atrial localization - Altun, Ozge; Akalin, Figen; Ayabakan, Canan; Karadağ, Bülent; Berrak, Su Gülsün; Bilal, Mehmet Salih; Ozek, Eren; Dağli, Elif (The Turkish Journal of Pediatrics, 2006)
Echinococcosis is a frequently encountered parasitic disease in the Mediterranean region, including Turkey. Cardiac disease is seen in 0.5-2% of patients. Usually the cysts are located within the pericardium or intramyocardially; intracavitary localization of the cyst is rarely seen. We herein report a patient who initially presented with hemoptysis and was echocardiographically diagnosed to have an intra-atrial hydatid cyst. Although patients with cardiac hydatid cysts may present with cardiac symptoms, symptoms typically involve other organ systems, following dissemination of the organism. Therefore, echocardiographic screening of patients who are diagnosed with echinococcosis, even if they have no cardiac symptoms, may ensure early diagnosis and prevent development of lethal complications, such as cyst rupture or embolization.